1936
DOI: 10.1085/jgp.19.5.739
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Ultraviolet Absorption Spectra of Certain Proteins and Amino Acids

Abstract: The ultraviolet absorption of the proteins in the region above 2500 A. comprises a broad band with its maximum about 2800 A. The spectrophotometric studies of Judd Lewis (1), Smith (2), and Smith and Marrack (3) have indicated the main quantitative features of this band without, however, disclosing evidence of finer structure. Indeed, with the exception of Spiegel-Adolf and Krumpel (4), who were able to distinguish several maxima in the absorption band of serum albu. rain, those investigators who have used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1937
1937
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Further biochemical analysis indicated little difference between A. gerardii and B. ischaemum leachate. Maximum absorbency of both leachates exhibited readings at~280 nm, indicating the presence of proteins (Coulter et al 1936). While aqueous and organic solubility were similar for A. gerardii and B. ischaemum leachate, it is possible that the allelopathic biochemicals are not pigmented, and may be organic soluble.…”
Section: Discussionmentioning
confidence: 92%
“…Further biochemical analysis indicated little difference between A. gerardii and B. ischaemum leachate. Maximum absorbency of both leachates exhibited readings at~280 nm, indicating the presence of proteins (Coulter et al 1936). While aqueous and organic solubility were similar for A. gerardii and B. ischaemum leachate, it is possible that the allelopathic biochemicals are not pigmented, and may be organic soluble.…”
Section: Discussionmentioning
confidence: 92%
“…It contains 12-5 % of tyrosine [du Vigneaud, 1938] and no tryptophan; 12-5% of cystine, which is all present in the disulphide form; and some phenylalanine. The ultra-violet absorption spectrum of insulin has been examined by several authors, and was found to resemble that of tyrosine [Kuhn, Eyer & Freudenberg, 1931;Coulter, Stone & Kabat, 1936;Graubner, 1938].…”
Section: Resultsmentioning
confidence: 99%
“…al. [43] and they have reported that aliphatic amino acids do not show absorption above 250 nm. Tyrosine tryptophan and phenylalanine show spectrum of absorption in the same spectral region as the proteins.…”
Section: Discussionmentioning
confidence: 99%